Identity and community in South African congregations - W. J. Schoeman (Acta Theologica)
The religious identity of both worshippers and congregations is not static, due to a changing context. Do congregational members believe, belong and engage in the same way as they did previously, or is it possible to track certain changes? Two Congregational Life Surveys were conducted in 2006 and 2010 among the membership of Dutch Reformed Church (DRC) congregations. The two surveys suggest that attenders prefer a private expression of their religion in which the Bible plays an important role. They have a strong bond with the congregation, but the preferred role of the congregation is to provide in the spiritual needs of the attenders. The engagement with the community is not so important for the attenders; in fact, the majority of them are not involved in the community. They value what the congregation does in the community, but personal involvement does not receive much attention. The biggest challenge for the reformation of a religious identity for both the membership and congregations of the DRC is to be more contextual and engaged in their social environment and culture. The two surveys suggest a movement in the opposite direction.